Comb-like PEG-containing polymeric composition as low toxic drug nanocarrier - Lesya Kobylinska; Igor Patereha; Natalia Finiuk; Natalia Mitina; Anna Riabtseva; Igor Kotsyumbas; Rostyslav Stoika; Alexander Zaichenko; Sandor G. Vari (Cancer Nanotechnology, 2018)
Abstract Background Development of biocompatible multifunctional polymeric drug carriers is crucial in modern pharmaceutics aimed to create “smart” drugs. The high potential of the PEGylated comb-like polymeric nanocarrier (PNC) in delivering both traditional and experimental drugs to tumor cells in vitro and in vivo has been demonstrated previously. In the present study, we investigated the general toxicity of polyethylene glycol (PEG) processed with both covalent and non-covalent attachments of PEG to compose a comb-like polymer that behaves like a simple chain of n monomers decorated with swollen side chains. The PNC possesses properties of a water-soluble surfactant containing methyl-terminated PEG side branches in some monomer units attached covalently to the carbon chain backbone. Results We have demonstrated that the synthesized PNC possesses weak toxic effects toward human leukemia cells (HL-60 and Jurkat lines), as well as toward hepatocellular (HepG2), colon (HCT116) and breast (MCF-7) tumor cell lines. Additionally, after a long period (20 days) of intraperitoneal administration, the PNC had no significant toxic effects in laboratory white mice (470 mg/kg body mass in 1 ml) and Wistar rats (440 mg/kg body mass in 10 ml). Conclusion The developed PNC we studied can be qualified as a compound of grade 4 toxicity (low toxicity substance). The reduced toxicity of this PNC in combination with its improved bioavailability and previously detected capability to enhance cytotoxicity toward tumor cells in vitro and potential tumor treatment effects in vivo suggests its potential as a safe drug delivery platform for treating various diseases, especially cancer.